Review Artikel: PENGGUNAAN FORMULASI NANOPARTIKEL KITOSAN SEBAGAI SISTEM PENGHANTARAN GEN NON VIRAL UNTUK TERAPI GEN - Lina Winarti (Fakultas Kedokteran Gigi Universitas Jember, 2011)
Gene therapy is a method to repair damaged or defective genes that responsible for the onset of certain diseases. Now, numerous prototypes of DNA can control the progress of the disease through induction or inhibition of genes, but the bad cellular uptake and the rapid in vivo degradation of DNA-based therapy require the use of delivery system that can facilitate the cellular internalization and keep its activity. Cationic polymers are commonly used as gene carrier because it is easy to form complexes and it has higher stability compared with lipoplexes. Cationic polymer chitosan is the most widely used in gene delivery system because of the low toxicity andbiocompatible. Gene delivery system using viruses shows high transfection result but it has many disadvantages, such as oncogenic effects and immunogenicity. However, cationic polymers, such as chitosan have the potential for complexation of DNA that can be used as a non-viral vector for gene therapy. Chitosan provides a strongelectrostatic interaction with negative charge of DNA to form nanoparticles and effectively protect from nuclease degradation. Those properties make chitosan become a good candidate from non viral gene delivery.